(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2006)
The present work describes a study of clinical case of a child with Deficit in Social Skills (DSS), developed by a therapist under formation, in accordance with the model of Child Behavior Therapy (CBT). The therapeutical handling relied basically on the report of contingencies, using techniques directed towards the Training in Social Skills (TSS). At the end of 20 sessions, some significant progress was reported, especially referred to the adjustment of the patient inside his environmental context. Despite the identified progress, the client maintained the standard of behavior governed by dysfunctional beliefs, and for this reason, the continuation of the therapy was recommended.